Compressive behaviour and design of prestressed steel elements. (February 2016) - Gosaye, Jonathan; Gardner, Leroy; Wadee, M. Ahmer; Ellen, Murray E.
Abstract: The tensile performance of the chords of steel trusses can be considerably enhanced through the addition of prestressed cables. However, under compression, which may arise due to wind uplift, the prestressing may have a detrimental effect. The behaviour and design of prestressed steel elements in compression is examined presently. Eight experiments on prestressed elements were carried out, where the key variables examined were the initial prestress level, the presence of grout and the member slenderness. Cross-sectional behaviour and member buckling behaviour are examined analytically, numerically and experimentally, with good correlation achieved between the three approaches. The benefit of adding grout to bond the prestressing steel to the encasing tube is also investigated and design approaches for both non-grouted and grouted prestressed elements are proposed.